Variation of turbulent kinetic energy due to dimples in intake manifold for diesel engine - Shahim Haider Abidi; M.M. Hasan (Case Studies in Thermal Engineering, 2021)
This work compares the application of spherical dimples in a modified intake manifold for the diesel engine to a normal intake manifold in terms of turbulent kinetic energy. In this work spherical dimples having an h/d ratio of 0.5 are used. These dimples had been designed by using designing tools in the design modeler module of ANSYS. Same bend angle condition 60° degree from the axis of manifold had been taken for both modified and normal intake system. The main purpose of this work is to observe the variation in turbulent kinetic energy due to the incorporation of spherical dimples in a intake model with a 20 mm diameter, 200 mm length and with a bend around 160 mm length. In this flow dynamics parameters other than turbulent kinetic energy like velocity and pressure were also observed. All numerical analyses were carried out on the FLUENT module of ANSYS and significant improvements of 25.45% and 35.41% for partial and full dimpled surface were reported in turbulent kinetic energy with respect to normal intake manifold, which were obtained due to modifications in the intake system. This work provides path to develop new techniques for enhancing mixing in the diesel engine.